Are doctors assessing patients with hypertension appropriately at their initial presentation? - Wong, Stalia Siew Lee; Ping, Yein Lee; Chirk, Jenn Ng; Hanafi, Nik Sherina; Yook, Chin Chia; Siew, Pauline Mei Lai; Su, May Liew; Ee, Ming Khoo (Stamford Publishing, 2015)
Background: The aim of this study was to determine the extent to which primary care doctors assessed patients newly diagnosed with hypertension for the risk factors of cardiovascular disease (CVD) during the patients’ first clinic visit for hypertension. The study also aimed to examine the trend of assessment for CVD risk factors over a 15-year period.